Developing drought resilience in irrigated agriculture in the face of increasing water scarcity - Rey, Dolores; Holman, Ian P.; Knox, Jerry W. (Springer, 2017)
In many countries, drought is the natural hazard that causes the greatest agronomic impacts. After recurrent droughts, farmers typically learn from experience and implement changes in management to reduce their future drought risks and impacts. This paper aims to understand how irrigated agriculture in a humid climate has been affected by past droughts and how different actors have adapted their activities and strategies over time to increase their resilience. After examining recent drought episodes from an agroclimatic perspective, information from an online survey was combined with evidence from semi-structured interviews with farmers to assess: drought risk perceptions, impacts of past drought events, management strategies at different scales (regional to farm level) and responses to future risks. Interviews with the water regulatory agency were also conducted to explore their attitudes and decision-making processes during drought events. The results highlight how agricultural drought management strategies evolve over time, including how specific aspects have helped to reduce future drought risks. The importance of adopting a vertically integrated drought management approach in the farming sector coupled with a better understanding of past drought impacts and management options is shown to be crucial for improving decision-making during future drought events.
Keywords: Adaptation; Drought management; Farmer; Water resources; UK